The Effect of Debt to Equity Ratio and Current Ratio on Return on Assets - Deti Susilawati; Firli Agusetiawan Shavab; Meri Mustika (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this study is to see how the Debt To Equity Ratio and Current Ratio affect the Return On Assets in pharmaceutical sub-sector manufacturing companies listed on the IDX from 2015 to 2019. Purposive sampling was used to determine the sample size in this study. Verificative and descriptive approaches were used in this study. Quantitative data analysis was used in this study. Based on the results of the partial test, it shows that the Debt To Equity Ratio has a significant negative effect on Return On Assets, and the Current Ratio has a significant positive effect on Return On Assets in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the IDX in 2015-2019. Simultaneously, the Debt To Equity Ratio and Current Ratio have a significant positive effect on Profitability (ROA) in Pharmaceutical Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in 2015-2019. The percentage contribution of the influence of Debt To Equity Ratio and Current Ratio to Return On Assets is 25%, while the remaining 75% can be explained by other factors not examined in this study.